A Project-Based Learning Approach to Measurement Systems Laboratory for Undergraduate Students - Meti, Vinod Kumar V.; Soori, Channavva; Talli, Amit; Giriyapur, A. C.; Revankar, Prashant; I. G., Siddhalingeshwar (Journal of Engineering Education Transformations, 2025)
Project-based learning (PBL) is one of the most effective teaching frameworks for undergraduate engineering courses due to its enormous advantages. The PBL approach facilitates active student engagement to a greater extent in laboratory courses as it can induce the process of complex and proactive thinking, problem-solving, and communication skills. This work presents pedagogical intervention in curriculum design and delivery of Measurement System Laboratory courses to undergraduate students in engineering. The study impacts assessing these new practices on student engagement and persistence in teaching-learning. The evaluation of student perception of the laboratory revealed that students enjoyed its execution, leading to improved academic performance and imbibing problem-solving skills. The PBL-laboratory exercise was a precursor to improvised student learning with self-directed initiatives working in teams. The study underlines excellent opportunities available through the reflection process that form the bedrock to strengthen their engineering laboratory practices. The detailed research strongly suggested PBL as the right way to engage students in the laboratory to fulfill curriculum needs.